Design and Comparison of Two Types of Antennas in the 2.45 Ghz Band to Calculate the Sar - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2021)
In this paper, we present the design of two different antennas with a band of 2.45 GHz, and their comparison, to calculate the SAR level for the IEEE 802.15.6. The first design consists on a dipole antenna with geometrics of a half wave. The second design is that of a rectangular microstrip antenna using the feedline method. Both of the antennas are designed with the goal of them working in wireless applications. The CST Simulator tool is used to examine the main characteristics of the antennas: return loss, VWSW, gain, and radiation pattern. In this research, we evaluate and compare the SAR levels of the dipole antenna with those of the microstrip antenna. In order to evaluate the maximum SAR levels, the antenna is used in a vertical position on a homogeneous model. In order to calculate the SAR levels for the tissues, we follow the two standards that are accepted nowadays by the FCC and ICNIRP. © 2021 IEEE.